Behavior of shallow concrete beams strengthened using low-cost GCSM and mechanical anchors - Phromphat Thansirichaisree; Hisham Mohamad; Mingliang Zhou; Ali Ejaz; Panumas Saingam; Qudeer Hussain; Suniti Suparp (AIMS Materials Science)
This study aimed to evaluate the shear strengthening capabilities of reinforced concrete (RC) shallow beams constrained by externally bonded glass chopped strand mat (GCSM) sheets and metallic mechanical anchors. The research investigated the effectiveness of GCSM sheets, known for their cost-effectiveness, ease of installation, and absence of specialized labor requirements, in improving the shear capacity, energy dissipation, and deformation capacity of RC beams. Experimental results revealed that GCSM sheets significantly enhanced the deformation capability, ultimate shear strength, and energy dissipation of RC shallow beams. Beams with GCSM applied to both the sides and bottom (SB) configuration demonstrated higher load-bearing capacity and energy dissipation compared to beams with GCSM only on the sides. The incorporation of a metallic mechanical bolt anchorage (MBA) system reduced the load-carrying capacities of beams with SB and beams with GCSM applied to only side by 28% and 5%, respectively, due to the drilling required for installation. However, the MBA system significantly improved the deflection performance, with beam B-S-A (GCSM on sides only and supplemented with MBA exhibiting the highest ultimate deflection of 23.92 mm. Overall, beams equipped with the MBA system showed superior ultimate deflection compared with those without it. Despite some reductions in load-bearing capacity, GCSM sheets combined with MBA systems proved highly effective in enhancing the shear strength, energy dissipation, and deformation capabilities of RC shallow beams, making them a valuable alternative for shear strengthening applications.